HUBUNGAN PERSONAL HYGIENE DENGAN PEDIKULOSIS KAPITIS PADA ANAK ASRAMA PUTRI SANTA LUSIA - Kriskayanti Habeahan; Novreka Pratiwi Sipayung; Rini Amanda C. Saragih; Poltak Poida B. Gurning (Jurnal Visi Eksakta, 2024)
Background: Pediculosis capitis is an infection of the skin and scalp hair caused by infestation of Pediculus humanus var capitis. This pediculus is ectoparasite that lives in the human head bye sucking the blood to survive. Personal hygiene is the risk factor for the pediculosis capitis. Objective: This study aims to determine the relationship of personal hygiene level with capitic pediculosis incidence of the female dormitory children of Santa Lucia Sei Rotan, district Percut Sei Tuan. Methods: The design used in this study was an observational analytic capproach cross sectional. The subject on this study were all of the children who were registered in the Santa Lucia dormitory, Sei Rotan, disctrict Sei Tuan. The technique used in this study are purposive sampling and Chi-square test data analysis. Collecting data through filling out questionnaires and direct examination of respondents. Results: The results of this study showed that 36 children (58.1%) suffered from pediculosis capitis, and children with good personal hygiene as many as 6 people (27.3%) suffered from pediculosis capitis, while in children with poor personal hygiene as many as 30 people (75%) suffers from pediculosis capitis. Chi-square test results found p = 0.000 value. Conclusion: There is a relationship between personal hygiene and the incidence of the Pedicolosis in the female dormitory children of Santa Lucia Sei Rotan, district Percut Sei Tuan. Keywords: Personal hygiene, Pediculosis capitis